Ocenjevanje skladenjskih napak v šolskem eseju - Velikonja, Irena (Jezik in slovstvo, 2018)
The article deals with syntax in school essays, focusing mainly on certain difficulties in syntax assessment. The first part presents the definition of syntactic mistakes according to the normative grammar. Syntactic structures that are not normatively incorrect but only (potentially) less appropriate are not defined as mistakes. The analysis of assessment shows that the distinction between actual mistakes and less appropriate forms is unclear, and that examiners' decisions on problematic syntactic forms are not unanimous. The last part of the paper presents a proposal for syntax assessment in the school essay.
Keywords: besedni red; matura; ocenjevanje; skladenjske napake; slog pisanja; slovenščina; šolski esej